2012
DOI: 10.1128/jvi.00612-12
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the Interferon and NF-κB Responses by Severe Fever with Thrombocytopenia Syndrome Virus

Abstract: e Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease characterized by high fever, thrombocytopenia, multiorgan dysfunction, and a high fatality rate between 12 and 30%. It is caused by SFTS virus (SFTSV), a novel Phlebovirus in family Bunyaviridae. Although the viral pathogenesis remains largely unknown, hemopoietic cells appear to be targeted by the virus. In this study we report that human monocytes were susceptible to SFTSV, which replicated efficiently, as shown by an immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
140
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(152 citation statements)
references
References 55 publications
6
140
2
4
Order By: Relevance
“…Thus, SFTSV NSs preferentially suppressed IRF3 but not NFkB activity in our setting. These results were at odds with a previous report (Qu et al, 2012), but might be more compatible with the overproduction of NFkB-induced cytokines in SFTSVinfected cells (Jin et al, 2015). Further studies are required to determine whether NFkB is activated by SFTSV.…”
contrasting
confidence: 57%
See 3 more Smart Citations
“…Thus, SFTSV NSs preferentially suppressed IRF3 but not NFkB activity in our setting. These results were at odds with a previous report (Qu et al, 2012), but might be more compatible with the overproduction of NFkB-induced cytokines in SFTSVinfected cells (Jin et al, 2015). Further studies are required to determine whether NFkB is activated by SFTSV.…”
contrasting
confidence: 57%
“…Consistent with this, SFTSV NSs protein has been shown to suppress type I IFN production through the interaction with RIG-I and TRIM25, as well as IRF3 kinases TBK1 and IKKe, leading to their sequestration in virus-induced cytoplasmic subdomains separated from mitochondria (Qu et al, 2012;Ning et al, 2014;Santiago et al, 2014;Wu et al, 2014). In addition, SFTSV NSs has recently been found to perturb type I IFN signalling by interacting with STAT2, and thus retaining STAT1 and STAT2 in the cytoplasm (Ning et al, 2015).…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Researchers have recently also found that SFTSV NSs had a similar effect on the viral multiplication, through the regulation of and escape from the host's innate immunity (15,16,20). Based on the physician's experience in clinical practice of SFTS treatment, it is unacceptable to give extrinsic IFN to SFTS patients due to the serious side effects of IFN administration, for example, severe fever, leukocytopenia, and thrombocytopenia, which are just the typical symptoms caused by SFTSV infection.…”
Section: Introductionmentioning
confidence: 99%